Understanding the Urbanization Process in Çine-Tepecik’s Cultural Development - Sevinç Günel (Anadolu Araştırmaları)
With its location on the Çine plain south of the Greater Meander (Büyük Menderes), Çine-Tepecik is a settlement that sheds light on the region’s early cultural history.Its earliest cultural remains date to the Chalcolithic Period (Late Neolithic in the Aegean chronology), and the settlement process extends to the end of the Late Bronze Age. In this chronological development, the pottery tradition, the art of depiction, and chipped stone technology are prominent lines of evidence characterizing Tepecik’s social life. Archaeological data show cultural and chronological development associated with Western Anatolia and the Aegean world. This interregional communication and cultural dynamism can be followed through vessels’ decoration style, cult items, and raw material sources since the Chalcolithic Period. Among raw materials sources, obsidian and flint were used in Chalcolithic, Early, Middle, and Late Bronze Periods. Obsidian in Tepecik was obtained from the Aegean islands and Central Anatolia, thus shedding light on the earliest interregional trade relations. Architectural remains of the settlement and its graves, which provide understanding of the Early Bronze Age’s burial tradition, evidence a society that has reached a certain sociocultural level. According to the mound’s stratigraphy, the settlement model with a defense system in the 2nd millennium BC, on the one hand, highlights Çine-Tepecik as a strong city in its region, but on the other hand, shows that cultural and commercial activities with Anatolia, the Aegean, and the Eastern Mediterranean are active. This communication reflects the art of figurative depictions, Mycenaean painted vessels, metal artifacts, and philological evidence from seal impressions in the Middle and Late Bronze Ages. In the Late Bronze Age settlement, the Mycenaean painted pottery tradition, with a rich group of finds, demonstrates that Tepecik played an important role in the Aegean region’s cultural network. In contrast, seal impressions with Anatolian hieroglyphs belonging to the Hittite Empire Period carry communication of the Tepecik settlement with the Hittites to official dimensions. In light of archaeological data and philological evidence, Çine-Tepecik contributes to the region’s archaeology with its strong position dominating natural roads in the south of Arzawa/Mira Land in Western Anatolia’s historical geography